UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL STRUCTURED NUMBERED HEADS (SNH) DI KELAS IX.5 SMP NEGERI 3 PANYABUNGAN - Asliati Asliati (Universitas Negeri Medan, 2018)
Abstract: Efforts to Improve Mathematics Learning Outcomes Using theStructured Numbered Heads (SNH) Model in Class IX.5 of Panyabungan StateMiddle School 3. This study originated from problems in Mathematics learning inclass IX.5 of Panyabungan State Middle School 3, where most students haddifficulty in understanding Mathematics learning material, so the learning outcomesobtained by students were also low. Therefore, to improve student learningoutcomes in Mathematics learning applied Structured Numbered Heads (SNH) TypeCooperative Learning Model to class IX.5 students of Panyabungan Middle School3. The results obtained in the first cycle of the average value obtained by newstudents reached 55% completeness with an average value of 68 students. While inthe second cycle showed a fairly high increase with an average value of 80 studentsand completeness 80%. Thus can it was concluded that the use of the StructuredNumbered Heads (SNH) Cooperative Learning Model succeeded in improvingstudent learning outcomes in Mathematics learning in class IX.5 of PanyabunganState Middle School 3.Keywords : Learning Outcomes, Mathematics, SNHAbstrak : Upaya Meningkatkan Hasil Belajar Matematika MenggunakanModel Structured Numbered Heads (SNH) Di Kelas IX.5 SMP Negeri 3Panyabungan Penelitian ini berawal dari permasalahan dalam pembelajaranMatematikadi kelas IX.5 SMP Negeri 3 Panyabungan,dimana sebagian besar siswamengalami kesulitan dalam memahami materi pembelajaran Matematika, sehinggahasil belajar yang diperoleh siswa pun rendah. Oleh karena itu, untuk meningkatkanhasil belajar siswa dalam pembelajaran Matematika diterapkan Model PembelajaranKooperatif Tipe Structured Numbered Heads (SNH) pada siswa kelas IX.5 SMPNegeri 3 Panyabungan ini. Hasil penelitian diperoleh pada siklus I nilai rata-ratayang diperoleh siswa baru mencapai ketuntasan 55% dengan nilai rata-rata siswa 68.Sedangkan pada siklus II menunjukkan peningkatan yang cukup tinggi dengan nilairata-rata siswa 80 dan ketuntasan 80%.Dengan demikian dapat disimpulkan bahwapenggunaan Model Pembelajaran Kooperatif Tipe Structured Numbered Heads(SNH) berhasil meningkatkan hasil belajar siswa dalam pembelajaran Matematikadikelas IX.5 SMP Negeri 3 Panyabungan. Kata Kunci : Hasil Belajar, Matematika, SNH